Sol-Gel Method for Preparation of Nanosize NiFe2-xCoxO4 Using Egg White - Situmeang, Rudy; Manurung, Posman; Try Sulistiyo, Septhian; Hadi, Sutopo; Simanjuntak, Wasinton; Sembiring, Simon (Asian Journal of Chemistry, 2015)
NiCoxFe2-xO4 nanomaterials (with x = 0.1-0.3) have been prepared using a combination method of sol-gel and freeze-drying. Preparation of material was carried out by dissolving nitrate salts of iron, nickel and cobalt in egg white solution and then the sample was stirred throughly using magnetic stirrer. The sample was subjected to calcination treatment and subsequently characterized using the techniques of X-ray diffraction for both qualitative and quantitative analysis such as Rietveld and Debye-Scherrer methods, infrared spectroscopy and scanning electron microscopy. The results of X-ray diffraction characterization indicated that the catalysts consist of various crystalline phases, with NiFe2O4 superimposed to CoFe2O4 is a major phase. FTIR analysis confirmed the existence of both Lewis acid and Brønsted-Lowry acid sites. The sample was found to display relatively surface morphology and according to the scanning electron microscopy data and Scherrer equation, the particle size of the material is in nano scale, 15-46 nm.